2018
DOI: 10.1111/scs.12566
|View full text |Cite
|
Sign up to set email alerts
|

Like an ace up the sleeve: an interview study of nurses’ experiences of the contact with relatives in a somatic emergency ward

Abstract: Research indicates that active involvement of patients' relatives generally has a positive impact on patients' hospitalisation, including patient safety. Campaigns urge relatives to ask questions in relation to nursing care and treatment to enhance patient safety and to increase involvement of both patient and relatives. The question is how nurses experience relatives who ask questions. The aim of this study was to explore how nurses experienced contact with patients' relatives during admissions to a somatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
0
13
0
5
Order By: Relevance
“…In a previous research, ED nurses found that working with families is either a bother or a benefit depending on whether the family members understand the healthcare system. 14 45 Furthermore, the HCPs discussed whether they were obligated to involve family members. The culture and attitudes influence how HCPs engage with families, and HCP training in communication skills is required to improve their relationship with families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous research, ED nurses found that working with families is either a bother or a benefit depending on whether the family members understand the healthcare system. 14 45 Furthermore, the HCPs discussed whether they were obligated to involve family members. The culture and attitudes influence how HCPs engage with families, and HCP training in communication skills is required to improve their relationship with families.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of family members in discharge information, such as medication and treatment adherence, has been acknowledged globally as a factor in improving patient outcomes 13 14. Moreover, family inclusion and partnership in care strengthen patients’ readiness for discharge 6.…”
Section: Introductionmentioning
confidence: 99%
“…9 10 In this care, family members play an active role in maintaining patient outcomes after early discharge to homes. 11 12 Mackie et al found in a qualitative study that health professionals identified the advantage of family participation in care for enhancing the quality of care and improving patient satisfaction. 13 14 However, research on the needs of family members involved in short visits to EDs is sparse or focuses on elderly patients.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The presence of relatives can be crucial for supporting older persons in various healthcare situations, as the social interaction includes both an exchange of information and collaboration between patients, nurses and relatives [2]. Relatives can act as social support, as they can reduce the patient's stress, increase the nurse's understanding, confirm instructions and agreements, promote communication between family members and work to preserve positive relationships between those involved [8]. However, a third person can prolong the conversation, as more information is usually needed, but also limit the exchange of information as the patient tends to leave the responsibility and social interaction to the relative.…”
Section: Introductionmentioning
confidence: 99%